2022
DOI: 10.1111/jce.15504
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high‐power short duration atrial fibrillation ablation in elderly patients

Abstract: Introduction: Data about atrial fibrillation (AF) ablation using high-power short duration (HPSD) radiofrequency ablation in the elderly population is still scarce. The aim of our study was to investigate the efficacy and safety of HPSD ablation in patients over 75 years compared to younger patients.Methods: Consecutive patients older than 75 years with paroxysmal or persistent AF undergoing a first-time AF ablation using 50 W HPSD ablation approach were analyzed in this retrospective observational analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Several studies have reported that RF catheter ablation for AF was safe and effective in elderly patients 9,13–19 . The safety and efficiency of AF patients aged >75 years were reported in the year of 2008 13 and those aged >80 years in the years of 2010 14 and 2012 15 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported that RF catheter ablation for AF was safe and effective in elderly patients 9,13–19 . The safety and efficiency of AF patients aged >75 years were reported in the year of 2008 13 and those aged >80 years in the years of 2010 14 and 2012 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Nademanee et al reported that catheter ablation for AF was associated with lower late stroke and bleeding event rates in patients aged >75 16 . These reports analyzed the results from ablation procedures that employed the technologies before the introduction of the latest ones, such as contact force‐sensing catheter 6–8 and quantitative ablation lesion size marker AI 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations